Mobile Health Applications for Trauma Management in the Middle East Region - Helsa Nasution; M. Agung Rahmadi; Rima Melati; Dinda Nurfadhilah; Siti Padila; Luthfiah Mawar; Nurzahara Sihombing; Sarah Mawaddah; Annisa Ardianti Br Tarigan (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
This meta-analysis assesses the effectiveness of mobile health (mHealth) applications in trauma management in the Middle East region, based on a systematic review of 47 empirical studies with a total of 12,486 participants published between 2015 and 2024. The quantitative synthesis results indicate that implementing mHealth has a statistically significant impact on improving trauma management, with a strong pooled effect size (g=0.78, 95% CI [0.65, 0.91], p<.001). Subgroup analyses reveal that the highest effectiveness is observed in interventions targeting Post-Traumatic Stress Disorder (PTSD) (g=0.86), followed by physical trauma management (g=0.74) and general psychological trauma (g=0.69). Further meta-regression findings identify the duration of application use (β=0.42, p<.001) and the level of intervention personalization (β=0.38, p<.01) as significant moderators influencing the magnitude of intervention effects. From an implementation perspective, user engagement reached 76.4%, and the retention rate was 68.2% after 6 months of use. Clinical outcome analyses demonstrate a significant reduction in PTSD scores with a mean difference of -14.6 points (p<.001) as well as a substantial improvement in quality of life (d=0.82). Comparatively, these findings extend the results of Goreis et al. (2020) and Kayrouz et al. (2018) by delineating more specifically the effectiveness of interventions in Middle Eastern populations. However, they differ from Yeager and Benight (2018) regarding the optimal duration of use. The principal contribution of this study lies in elucidating the central role of cultural adaptation, which shows a strong correlation with the effectiveness of mHealth applications (r=0.56, p<.001) in the context of trauma management in the Middle East.